Comparison of the EORTC tables and the EAU categories for risk stratification of patients with nonmuscle-invasive bladder cancer - Rieken, Malte; Shariat, Shahrokh F; Kluth, Luis; Crivelli, Joseph J; Abufaraj, Mohammad; Foerster, Beat; Mari, Andrea; Ilijazi, Dafina; Karakiewicz, Pierre I; Babjuk, Marek; Gönen, Mithat; Xylinas, Evanguelos (Urologic oncology, 2018)
PURPOSE: To characterize outcomes of patients with TaT1 urothelial carcinoma of the bladder stratified by the European Association of Urology (EAU) categories and to compare them with European Organization for Research and Treatment of Cancer (EORTC) risk groups to assess the rate and effect of reclassification. PATIENTS AND METHODS: A multi-institutional database of 5,122 patients with TaT1 urothelial carcinoma of the bladder who underwent transurethral resection of the bladder with or without adjuvant therapy at 8 institutions between 1996 and 2007. Multivariable Cox-regression analyses addressed factors associated with disease recurrence and progression. The net reclassification index was used to compare the performance of the EAU categories with the EORTC scoring system. RESULTS: Of 5,122 patients, 632 (12.3%), 2,302 (45.0%), and 2,188 (42.7%) were assigned to the low-, intermediate-, and high-risk EAU category, respectively. Within a median follow-up of 62 months (interquartile range: 27-97), 2,365 (46.2%) and 516 (10.1%) patients experienced disease recurrence and progression, respectively. In multivariable Cox-regression analyses, EAU intermediate- and high-risk categories were associated with a higher risk of disease recurrence (P<0.001) and progression (P<0.001) compared to low-risk patients. Application of the EAU categories reclassified 1,940 (37.9%) patients into a higher risk group for recurrence. Likewise, 602 (11.8%) patients were reclassified to a higher and 278 (5.4%) to a lower risk group for progression. The net reclassification index of the EAU risk stratification was 0.1% (95% CI: -3.1% to 3.2%) for recurrence and 10.1% (95% CI: -8.0% to 12.0%) for progression, respectively. CONCLUSIONS: Compared to EORTC risk stratification, the EAU categories reclassifies 37.9% patients into a higher risk group of recurrence and 11.8% into a higher risk of progression. However, the novel risk stratification assigns most patients to the same treatment as the more complex EORTC tables and can be regarded as an alternative tool for treatment decision-making.
Keywords: Humans; Recurrence; lokální recidiva nádoru; nádory močového měchýře; Risk-Taking; Risk Factors; Prediction; mužské pohlaví; Non-muscle invasive; Neoplasm Recurrence, Local; Disease Progression; Progression; výsledek terapie; rizikové faktory; Urinary Bladder Neoplasms; Treatment Outcome; Bladder cancer; ženské pohlaví; Risk stratification; lidé; Aged; senioři; progrese nemoci; riskování; Male; Female